2017
DOI: 10.1155/2017/3015120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Supplementation with Prebiotic, Oregano Extract, and Vitamin E on Fatty Acid Profile and Oxidative Status of Rabbit Meat

Abstract: The effect of dietary supplementation with vitamin E, oregano, and prebiotic on fatty acids and oxidative profiles of rabbit meat (loin and hind leg) was evaluated. New Zealand white rabbits weaned at 30 days of age were fed with one of six diets until 80 days of age: standard diet including 3 polyunsaturated fatty and conjugated linolenic acids sources (S) and five diets adding vitamin E (150 ppm, E), oregano water extract (2 g/kg feed diet, O), prebiotic (THEPAX5 1.5 g/kg feed diet, T), vitamin E plus prebio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The role of VE as an antioxidant is well known and some authors have highlighted a parallel positive effect on total PUFA content (Castellini et al, 2001;Lopez-Bote et al, 1997). Although the VE effect on PUFA content did not emerge in this study, similarly to those of other authors (Lopez-Bote et al, 1997;Corino et al, 2007;Mattioli et al, 2017), its protective effect on oxidative stability was strongly confirmed (Castellini et al, 2001;Lo Fiego et al, 2004;Corino et al, 2007), and in the BF already evident at the lowest concentration.…”
Section: Fa Composition Of Ll and Bfsupporting
confidence: 79%
“…The role of VE as an antioxidant is well known and some authors have highlighted a parallel positive effect on total PUFA content (Castellini et al, 2001;Lopez-Bote et al, 1997). Although the VE effect on PUFA content did not emerge in this study, similarly to those of other authors (Lopez-Bote et al, 1997;Corino et al, 2007;Mattioli et al, 2017), its protective effect on oxidative stability was strongly confirmed (Castellini et al, 2001;Lo Fiego et al, 2004;Corino et al, 2007), and in the BF already evident at the lowest concentration.…”
Section: Fa Composition Of Ll and Bfsupporting
confidence: 79%
“…Previously there have been many studies/reviews concerning rabbit meat, including its production, quality, physicochemical properties and composition [ 1 , 2 ]. A lot of them dealing with the effects of dietary supplementation with functional compounds, mainly probiotics, prebiotics, fatty and organic acids, vitamins, selenium and antioxidants and their combinations on rabbit carcass quality [ 12 , 13 , 14 , 31 , 33 , 40 , 87 , 88 , 89 ]. In general, there is a lack of studies testing the beneficial microbiota and/or their antimicrobial substances (bacteriocins) on rabbit meat quality and composition, including fatty acids, amino acids and minerals [ 31 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Application Effects Of E Faecium Ccm7mentioning
confidence: 99%
“…Similarly, the influence of dietary garlic extracts on fatty acid synthesis has been reported in Acipenser ruthenus and M. rosenbergii (Aarumugam et al, 2013;Lee et al, 2012). Previously, administration of spirulina (Arthrospira platensis) and/ or thyme (Thymus vulgaris) in the diets of Oryctolagus cuniculus (New Zealand white rabbit) showed significant changes in fatty acid contents (Mattioli et al, 2017). Similar results have also been reported in M. rosenbergii PL fed on garlic, ginger, turmeric, and fenugreek extracts in the supplemented diet (Poongodi, 2011).…”
Section: Fatty Acid Profilementioning
confidence: 81%